The Impact of Technology Utilisation on The Effectiveness of Internal Control System Work at BP Batam - Rahmi Ramadhani; Lawita, Nadia Fathurrahmi (LPPM Universitas Pelita Bangsa, 2025)
This study analyses the impact of technology utilisation on the effectiveness of the Internal Control System (ICS) at BP Batam. Using a mixed-method approach, data was collected through questionnaires distributed to all 32 staff members of the internal audit unit and interviews with department head and sub-department head. Quantitative results indicate that the use of technology, particularly the B-Audit system, significantly enhances the effectiveness of the ICS by improving data accuracy, decision-making speed, and transparency. Qualitative findings further confirm the critical role of technology in supporting internal control functions, supported by adequate facilities, communication channels, and responsive IT support. Despite challenges such as the adaptation of some employees nearing retirement and the need for better audit standar implementation, the overall contribution of technology to SPI at BP Batam is positive. Recommendation includes enhanced training, strengthened infrastructure, and system integration to maintain and maximise the benefits of technology in internal control.